Key Essentials of Effective English Language Teaching (SNPRC Journal, 2025)
Effective teaching and learning remain a central concern in education and constitute a significant focus in English language education. Drawing on extensive review of the relevant literature and the author’s own teaching experiences, this paper identifies and discusses six key essentials that contribute to effective English language teaching: dynamic and agentive role of teachers, active and autonomous learners who take responsibilities for their own learning, context sensitive methods and strategies that critique one-size-fits-all methodological orientation, strategic use of no-cost and low-cost instructional resources which address learner’s specific needs, integration of information and communication technology and valid and reliable assessments to ensure fair evaluation of student’s learning outcomes. The paper implies that effective English language teaching requires the efficacy of all components so as to foster holistic approach and contribute to offer enhanced pedagogical practices.